Абсолютна маса насіння і збирання льону-довгунця - Лімонт, А. С.; Поліщук, О. С.; Плужніков, О. Б.; Limont, А.; Polishchuk, О.; Pluzhnikov, О. (КНТУ, 2016)
Узагальнені експериментальні дані про абсолютну масу насіння льону-довгунця з урахуванням фаз його стиглості і їх тривалість. З’ясовані кількісні зміни абсолютної і відносної вологості залежно від фаз стиглості за числом днів їх настання від зеленої. The paper is aimed at enhancino the efficiency of fiber flax mechanized production through introducing promising technologies of harvesting which provide for obtaining the maximum yield, long fiber count and highquality seeds by its absolute mass. On the basis of the references cited the paper highlights the investigations into the empirical distribution of the absolute mass of seeds of fiber flax which is harvested under its green, early yellow, yellow and complete ripeness. Consideration is given to the range of variations in the absolute mass of seeds, its arithmetical mean, average quadratic deviation and the coefficient of variation. The authors determine the correlation of average quadratic deviations of the asymmetry coefficients, as well as the excess related to these coefficients. On the basis of the calculations and with respect to the value of χ-square of Pirson criterion one can prove the insignificance of the differences between empirical distributions and the standard law. When applying the peculiarities of the standard distribution one can reveal the probability of obtaining seeds with appropriate absolute mass which determines its sowing quality. The paper also generalizes the information related to reaching the appropriate phases of ripeness with respect to the number of days beginning from the green phase. The authors specify the character of the quantitative changes in the absolute mass of seeds and in the absolute and relative humidity of seeds boxes expending on the phases of fiber flax ripeness with respect to the number of days beginning from the green ripeness which makes it possible to determine the corresponding method of harvesting and the organization of flax harvesting process. Depending on the duration of fiber flax harvesting process the change in the absolute mass of fiber flax seeds is presented by the equation of moderated ascending logarithmic function, and the absolute and relative humidity of seed boxes – by the equation of lines with negative angle coefficients.
The absolute mass of seeds and fiber flax harvesting
Keywords: льон-довгунець; насіння; абсолютна маса; фази стиглості; збирання; дні; закономірність; fiber flax; absolute mass; phases of ripeness; harvesting; days; regularity